A Thematic Review of Graffiti Subculture Research (2020–2025): Space, Resistance, and Identity - Zhang, Jimin; Ismail, Zuhaili Akmal; Lee, Luqman (Advances in Social Sciences Research Journal, 2025)
Graffiti has long been considered an artistic practice and a form of social expression. In recent years, research on graffiti subculture has grown, with scholars exploring its role in shaping urban space, supporting social movements, and preserving cultural memory. However, despite this growing body of research related to graffiti subculture, a comprehensive review of research topics from 2020 to 2025 remains lacking. This article aims to address this gap by synthesizing relevant literature on graffiti subculture from 2020 to 2025 using the ATLAS.ti 8 system. A keyword search and inclusion criteria were applied to the Art & Architecture Complete and Scopus databases, resulting in the identification of 56 peer-reviewed journal articles. However, after this screening process, only 27 articles were included. A thematic review of these 27 articles identified 13 initial codes, which were clustered into three themes: Graffiti and the Reconstruction of Urban Space; Graffiti’s Practice in Social Movements and Protests; and Graffiti’s Emotional Memory and Identity Construction. The results of this study contribute to future research on graffiti subculture and demonstrate the potential of graffiti at the intersection of creativity and commercialization, empowerment and co-optation, and emotional memory and identity. This study will also guide future research on graffiti subculture.